Efektivitas Layanan Bimbingan Kelompok Menggunakan Teknik Motivational Interviewing Untuk Peserta Didik Pecandu Game Online Dengan Kecenderungan Loneliness - Fyarisa; Akhyar Lubis, Saiful (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to determine the effectiveness of group guidance services using the Motivational Interviewing (MI) technique in reducing the level of online game addiction and loneliness tendencies in students. The method used is a quantitative approach with a One Group Pretest-Posttest design. The research sample consisted of 13 students of class X-10 of SMA Negeri 1 Sunggal who were indicated to be addicted to online games with a tendency to loneliness. Data collection was carried out through questionnaires, observations, interviews, and documentation. The results of data analysis using the Paired Samples T-Test showed a significant difference between the pretest and posttest scores for both online game addiction and loneliness variables, with a significance value of 0.000 (p <0.05). This shows that group guidance services with the Motivational Interviewing technique are effective in reducing online game addiction and reducing loneliness in students.